Chapter 1 The Articles of Faith of Citizen Aid Actors - between Dreams and Realities - Kinsbergen, Sara (Taylor & Francis, 2023)
Over the years, established NGOs have been increasingly criticised for losing their role as transformational powers because of processes of (among others) professionalisation and bureaucratisation and, related to this, increased dependence on government funding. The organisational features of citizen aid are what distinguish them from established development organisations. Are the small and voluntary organisations run by citizens as a consequence and contrary to their established counterparts, not 'too close for comfort' and able to live up to the 'articles of faith' as distinguished by Tendler? This first chapter introduces the book, the two parts and the different chapters and authors. More importantly, it sets the stage by discussing the emergence of citizen aid particularly in the field of international cooperation and the many different ways they are related to other development actors, and bringing together the different names and concepts with which this phenomenon has been studied over the last decade and which are used in this book. All the research that has gone into private development organisations (mainly under the name of NGO studies) has provided little insight into broader groups of these NGOs and has been focused primarily on a few big organisations. In effect, we acknowledge the diversity in the sector but, in fact, know relatively little about that same diversity. This volume tackles that shortcoming of the existing literature. We study the rise of citizen aid as part of the changing aid architecture, with a clear folk to folk dimension, which includes aspects of solidarity and global citizenship. We discuss how the alternative nature of this actor, being small in scale and voluntary, determines their role as development actors.